Hybrid Thermophilic/Mesophilic Enzymes Reveal a Role for Conformational Disorder in Regulation of Bacterial Enzyme I. Issue 16 (24th July 2020) - Dotas, Rochelle R.; Nguyen, Trang T.; Stewart, Charles E.; Ghirlando, Rodolfo; Potoyan, Davit A.; Venditti, Vincenzo
Abstract: Conformational disorder is emerging as an important feature of biopolymers, regulating a vast array of cellular functions, including signaling, phase separation, and enzyme catalysis. Here we combine NMR, crystallography, computer simulations, protein engineering, and functional assays to investigate the role played by conformational heterogeneity in determining the activity of the C-terminal domain of bacterial Enzyme I (EIC). In particular, we design chimeric proteins by hybridizing EIC from thermophilic and mesophilic organisms, and we characterize the resulting constructs for structure, dynamics, and biological function. We show that EIC exists as a mixture of active and inactive conformations and that functional regulation is achieved by tuning the thermodynamic balance between active and inactive states. Interestingly, we also present a hybrid thermophilic/mesophilic enzyme that is thermostable and more active than the wild-type thermophilic enzyme, suggesting that hybridizing thermophilic and mesophilic proteins is a valid strategy to engineer thermostable enzymes with significant low-temperature activity. Graphical abstract: Unlabelled Image Highlights: EI is a central regulator of bacterial metabolism and a promising drug target. The C-terminal domain of EI exists as a mixture of active and inactive conformations. Functional regulation is attained by diluting the active enzyme with inactive states. We design hybrid thermophilic/mesophilic EI with enhanced low-temperature activity.